Economic Growth, Population Density, and Human Development: Key Drivers of Environmental Quality in Indonesia - Soeparno, Wahyu Sugeng Imam; Anggia, Yola; Sari, Raina Linda; Purba, Febry Andini (Research Parks Publishers, 2024)
In an effort to understand the interactions between economic growth, population density, the Human Development Index (HDI), and the Environmental Quality Index (EQI) in Indonesia, this study adopts a quantitative approach utilizing panel data encompassing 34 provinces during the period from 2020 to 2022. This analysis implements fixed effects models in panel data regression to isolate the impact of these variables on environmental quality. Results indicate that neither economic growth nor population density significantly affect the EQI, while an increase in HDI significantly contributes to environmental improvement, emphasizing the importance of factors such as education, health, and living standards. Furthermore, the cross-section fixed effects analysis reveals significant provincial-specific factors influencing the EQI, which macroeconomic and demographic variables cannot fully explain. Variability among provinces shows that some have a strong positive effect on the EQI, whereas others have a negative impact, highlighting the need for regionally tailored policies to enhance effectiveness in environmental conservation efforts. These findings inform policymakers about the importance of focusing on human development as a key element in strategies to improve environmental quality in Indonesia. The implications suggest that sustainable development strategies must integrate aspects of human development with comprehensive environmental policies, creating synergies that support environmental preservation. This study makes a significant contribution to the literature by providing insights into effective ways that Indonesia can adopt to address current and future environmental challenges.